2016
DOI: 10.1055/s-0042-112029
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Individual Analysis of Post-Exercise Hypotension Following a Single Bout of High-Intensity Interval Exercise and Continuous Exercise: A Pilot Study

Abstract: Recently, post-exercise blood pressure (BP) has been considered a predictive tool to identify individuals who are responsive or not to BP reductions with exercise training (i. e., "high" and "low responders"). This study aimed to analyze the inter- and intra-individual BP responsiveness following a single bout of high-intensity interval exercise (HIIE) and continuous exercise (CE) in normotensive men (n=14; 24.5±4.2 years). Mean change in BP during the 60 min period post-exercise was analyzed and minimal detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
6
46
0
5
Order By: Relevance
“…Cohen's formula for effect size (ES; [9]) was used, and the results were based on the following criteria; > 0.70 large effect; 0.30-0.69 moderate effect; ≤ 0.30 small effect. Minimal detectable change (MDC) was calculated as: MDC = Z-score (90 % CI) × SEM × √2 according to Costa et al [10]. Data are presented as mean ± SEM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cohen's formula for effect size (ES; [9]) was used, and the results were based on the following criteria; > 0.70 large effect; 0.30-0.69 moderate effect; ≤ 0.30 small effect. Minimal detectable change (MDC) was calculated as: MDC = Z-score (90 % CI) × SEM × √2 according to Costa et al [10]. Data are presented as mean ± SEM.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a minimal detectable change (MDC) analysis of the blood pressure response because it has been reported that PEH may be a heterogeneous physiological phenomenon with responders and non-responders, rendering it impossible to appreciate the potential effects of different exercise methods (i. e., continuous vs. interval [10]) on PEH. However, 10 out of 14 subjects (71 %) responded to HIIT with detectable reductions in systolic blood pressure, whereas only 3 out of 14 (21 %) responded with reductions after CE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated PEH, but they have applied different BP values as control levels (i. e. pre-exercise levels or BP measured on a control day without exercise) and have employed different ways of calculating PEH. In many studies [5,11,12,16,25], BP has been measured before and after an exercise bout, and PEH has been calculated as the difference between post-and pre-exercise BP (PEH_I = post-exercise BP − pre-exercise BP). In other studies [4,13,14,19,22], BP has been measured after an exercise and a control session, and PEH has been calculated as the difference between post-exercise and post-control BP (PEH_II = post-exercise BP − post-control BP).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomena is described as post-exercise hypotension and it is observed both acutely and chronically as a body physiological consequence of exercise. 63 Acutely, it has been reported reductions of BP in both aerobic and resistance training. 64,65 Chronically, previous studies found that regularly-performed PE is associated with reductions of 8.3 and 5.2 mmHg in resting systolic and diastolic BP, respectively.…”
Section: Peripheral Effectsmentioning
confidence: 99%